2014
DOI: 10.1177/0743558414565236
|View full text |Cite
|
Sign up to set email alerts
|

“She Posted It on Facebook”

Abstract: We examined experiences with technology and dating conflict among Mexican American (MA) adolescents (ages 15-17 years) using mixed qualitative methodologies. Focus groups, divided by three levels of acculturation and gender (N = 20), and videotaped observations of couples (N = 34), found that technology (i.e., cell phones, social media) afforded adolescents increased visibility of their partners' day-to-day peer interactions. Feelings of romantic jealousy resulted in text message harassment and the expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…Reading social media feeds could also breed relationship jealousy. In a qualitative study with Mexican American adolescents, use of digital communication was associated with jealousy in romantic relationships and with mistrust due to online surveillance of partners’ activities (Rueda, Lindsay & Williams, 2015). …”
Section: Less Obvious Forms Of Digital Harm: the Potential Pain Of Lumentioning
confidence: 99%
“…Reading social media feeds could also breed relationship jealousy. In a qualitative study with Mexican American adolescents, use of digital communication was associated with jealousy in romantic relationships and with mistrust due to online surveillance of partners’ activities (Rueda, Lindsay & Williams, 2015). …”
Section: Less Obvious Forms Of Digital Harm: the Potential Pain Of Lumentioning
confidence: 99%
“…Participants described conflict, jealousy, reductions in trust, and a belief that app use decreased their partner's focus on their relationship, which have been reported among heterosexual samples (Clayton, 2014; Hertlein & Ancheta, 2014; McDaniel & Coyne, 2014; Rueda et al, 2014). We also found that jealousy and trust issues were referenced primarily in context of breaks in the couple's relationship agreement (e.g., not checking with main partner prior to a sexual encounter with a partner met through the app), or when prospective sexual partners who couples met through the app gave a disproportionate amount of attention to one partner.…”
Section: Discussionmentioning
confidence: 84%
“…Although past research has often focused on the adverse impact GSN apps can have on heterosexual relationships (Clayton, 2014; Coyne et al, 2011; Hertlein & Ancheta, 2014; McDaniel & Coyne, 2014; Rueda et al, 2014), the current study offers insight into ways that same-sex male couples can utilize such tools to fulfill each other's social and sexual needs. Although GSN app use can enhance relationships and sex among partnered MSM, unclear communication about app use may contribute to negative relationship outcomes and could prevent partners from having sexual needs met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aim of this study is to address this need for additional research by exploring the different ways in which adolescents perceive social media as capable of eliciting feelings of jealousy, conflict and irritation, monitoring behaviors, as well as adolescents' responses to these feelings. Some exploratory studies have examined these issues (Lucero et al, 2014;Rueda et al, 2015;Van Ouytsel, Van Gool, et al, 2016). However, more information on the ways that technology use is linked with abusive behaviors within adolescent romantic relationships is warranted, to better assist relationship development (Baker & Carreño, 2016).…”
Section: The Present Studymentioning
confidence: 99%